1999
DOI: 10.1007/s002210050697
|View full text |Cite
|
Sign up to set email alerts
|

Deafferentation and pointing with visual double-step perturbations

Abstract: The capability of reprogramming movement responses following changes in the visual goal has been studied through the double-step paradigm. These studies have shown that: (a) continuous internal feedback-loops correct unconsciously the dynamic errors throughout the movement; (b) proprioceptive information and/or the efference copy have a privileged status among central processes, insuring on-line regulation of the initial motor commands; and (c) generation of the motor program starts after target presentation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
42
0
2

Year Published

2003
2003
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(45 citation statements)
references
References 34 publications
1
42
0
2
Order By: Relevance
“…However, it can be taken for granted that the ''sensory-motor transformation'' requires proprioceptive as well as exteroceptive feedback: For example, Cole (1995) describes in his book ''Pride and the Daily Marathon'' how a deafferented patient is unable to maintain an upright position in darkness, which reveals that proprioceptive feedback is indispensable even for the simplest motor control (cf. also Jeannerod 1988; Bard et al 1999;Sainburg et al 1993;Cole and Paillard 1995). And, in an experiment by Proteau et al (1987) blocking of visual feedback causes more disturbances after 2,000 than after 200 repetitions of a simple grasping movement, which shows that exteroceptive (visual) feedback is indispensable even for the simplest movements.…”
Section: On the Role Of Feedback In Behavioral Controlmentioning
confidence: 93%
“…However, it can be taken for granted that the ''sensory-motor transformation'' requires proprioceptive as well as exteroceptive feedback: For example, Cole (1995) describes in his book ''Pride and the Daily Marathon'' how a deafferented patient is unable to maintain an upright position in darkness, which reveals that proprioceptive feedback is indispensable even for the simplest motor control (cf. also Jeannerod 1988; Bard et al 1999;Sainburg et al 1993;Cole and Paillard 1995). And, in an experiment by Proteau et al (1987) blocking of visual feedback causes more disturbances after 2,000 than after 200 repetitions of a simple grasping movement, which shows that exteroceptive (visual) feedback is indispensable even for the simplest movements.…”
Section: On the Role Of Feedback In Behavioral Controlmentioning
confidence: 93%
“…These results suggested that the desired state issued from the inverse models and the predicted dynamic state issued from the forward dynamic models could be compared to control the movement before availability of the sensory afferences. Finally, these sensory afferences become available to adjust the ongoing trajectory onto the sensory prediction of the forward sensory models, when necessary (Bard et al 1999;Branch Coslett et al 2008;Desmurget et al 1999;Farrer et al 2003;Hansen and Elliott 2009;Miall and Wolpert 1996;Wolpert and Ghahramani 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Hand movements can be updated without awareness of the target's shift, such as during ocular saccades (Blouin et al, 1995), and in the absence of visual control (Pélisson et al, 1986) or limb proprioception (Bard et al, 1999;Sarlegna et al, 2006). Online corrections might rely on a nonsensory feedback mechanism based on motor outflow (Desmurget and Grafton, 2000), as well as on sensory information (Blouin et al, 1995;Desmurget et al, 1999).…”
Section: Introductionmentioning
confidence: 99%